(untitled) (Singaporean Journal of Business Economics and Management, 2024)
To provide organizations with pertinent figures and information to enhance leadership efficacy and employees’ well-being, this study investigates the connection between leadership lapses and their impact on employees’ well-being and performance. Employee motivation and organizational culture are greatly influenced by leadership. Leadership lapses can result in lower production, higher attrition, and lower well-being of employees. The fundamental mechanics of this link are examined in this study, along with empirical data from many kinds of research, surveys, and recommendations for organizations looking to increase employee well-being and leadership effectiveness. Data on employee perceptions of leadership effectiveness and its relationship to well-being and performance are gathered using a mixed-method approach during the study. In this regard, 400 respondents, comprising 218 male and 182 female employees from various government and semi-government organizations of Pakistan were nominated, they were given questionnaires / asked questions on leadership lapses and how they impact workers’ well-being and performance. As a result, it was found that there was a strong correlation between leadership lapses and the well-being of employees and their performance. Numerous viewpoints, theories, and paradigms were also looked for during the inquiry. The study’s findings, which included workers’ well-being and leadership lapses, showed how poor leadership seriously impairs worker engagement and the organization’s output.